(untitled) (Gaceta Técnica, 2022)
Curing is of vital importance in concrete since it consists of its setting and hardening over time, in order to obtain optimum compressive strength. The objective of this research was to determine the curing method that allows reaching the highest resistance at 28 days. Three different types were used, these are: continuous hydration, wet covers and polyethylene sheets; for each of them, nine cylindrical specimens were made applying the NTE INEN 1576:2011, the compressive strength tests were carried out, applying the NTE INEN 1573:2010, at 7, 14 and 28 days in order to analyze the witness behavior. The design strength was f’c= 21MPa, the compressive strength tests showed that the method with the greatest benefit for the concrete was that of wet cover, reaching a strength value of 22.92 MPa after 28 days with relationship to design f’c.